Effects of colloid preload on the incidence of hypotension in spinal anesthesia for cesarean section: a systematic review and meta-analysis. Issue 9 (5th May 2021) - Gong, Rui-Song; Liu, Xiao-Wen; Li, Wei-Xia; Zhao, Jing
Abstract: Background: Hypotension is a common complication caused by spinal anesthesia (SA), which may have adverse impacts on the condition of the parturient and fetus. Liquid infusion was found to be relatively effective for reducing the incidence of hypotension. However, the question of whether colloid preload can optimize hemodynamic variables in the cesarean section remains controversial. This study aims to determine the effects of colloid preload on the incidence of hypotension induced by SA in elective cesarean section. Methods: Related keywords were searched on PubMed, EMBASE, and Cochrane Library from inception dates to May 2020. Studies included were evaluated for eligibility and quality. The primary outcome was the intra-operative incidence of hypotension and severe hypotension. The secondary outcomes included the lowest intra-operative systolic blood pressure, the maximal intra-operative heart rate, the intra-operative needs of ephedrine and phenylephrine, the incidence of maternal nausea and/or vomiting, and neonatal outcomes (umbilical artery pH and Apgar scores). Apart from the above, RevMan 5.3 was used for the data analysis. Results: Altogether nine randomized controlled trials were included in the meta-analysis. There were no significant differences in the incidence of intra-operative hypotension, severe hypotension, or neonatal outcomes between the colloid preload group and control group, except for the umbilical artery pH. Conclusion: This meta-analysis suggests that colloid preload does not significantly reduce the incidence of hypotension associated with SA in elective cesarean section.